A case of grade 3 squamous cell carcinoma successfully treated with methotrexate - Giovanni Sarracco; Fabio Rinaldi; Francesco Cusano (PAGEPress Publications, 2024)
Cutaneous squamous cell carcinoma (cSCC) is a nonmelanoma skin cancer whose lesions mostly arise on lightexposed sites. Patients with compromised immunity, Fitzpatrick I or II skin phototype, and previous burn scars or radiations are more at risk of developing it. The treatment of choice for cSCC is surgery; however nonsurgical options are generally reserved for patients who refuse a very invasive treatment or cannot tolerate a surgical procedure. We report a case of cSCC successfully treated with intralesional methotrexate.